HOW TO TRANSFER COMPETENCIES INTO THE LEARNING CONTENT - Nikolay V. Sosnin (Moscow Polytechnic University, 2016)
The article discusses the problem of content structure of competence2oriented learning. It is argued that the key issue in this problem is the way to transfer competencies of a graduate into learning content of educational program. Integrative and beyond2disciplinary nature of the competencies requires changes to traditional disciplinary model. A concept is proposed, according to which firstly the structure of the learning outcomes is designed and then it turns into the content of the structural units of the learning process.